Meroterpenes from Psoralea corylifolia against Pyricularia oryzae - Huang, Youwu; Liu, Xiaoyu; Wu, Yingchun; Li, Yiming; Guo, Fujiang (Planta Medica, 2014)
Six new meroterpenes, namely, 13-methoxyisobakuchiol (1), 13-ethoxyisobakuchiol (2), 12,13-dihydro-13-hydroxybakuchiol (3), Δ10-12,13-dihydro-12-(R,S)-methoxyisobakuchiol (4 and 5), and 15-demetyl-12,13-dihydro-13-ketobakuchiol (6), together with four known ones, namely, Δ3,2-hydroxybakuchiol (7), Δ1,3-hydroxybakuchiol (8), bakuchiol (9), and Δ1,3-bakuchiol (10), were isolated from the seeds of Psoralea corylifolia. Their structures were identified based on spectral data, including those obtained via 1D and 2D NMR, and MS spectral analyses. Antifungal screening results indicated that all compounds showed moderate inhibitory activities against Pyricularia oryzae.
Keywords: Psoralea corylifolia; Fabaceae; meroterpenes; antifungal; Pyricularia oryzae